Promoting Character Education through Narratives - Gusti Putu Rustika Dewi; Ni Komang Arie Suwastini; Zhu Minxia; I Gusti Agung Sri Rwa Jayantini; Ni Nyoman Artini (Mimbar Ilmu, 2026)
The use of narratives as a means of promoting character education is an academic effort to address the current decline in general character among younger generations. However, previous research on the use of stories in character education has not been comprehensively reviewed. This study was a qualitative library research, following the principles of source selection, evaluation, and synthesis proposed by George (2008) which aimed (1) to explore forms of narratives used to teach character values, (2) to investigate methods to teach character values, and (3) to explore the character values in narratives. This study selected 36 articles from previous studies published between 2015 and 2024. The subject of this research were articles sourced from indexed journals listed in Scopus, Science and Technology Index (SINTA) 3, and Web of Science (WoS). The results of the study showed that forms of narratives used to teach character values in relation to character education were mainly in the forms of animation movies, fables, fairy tales, folklore, comics, narrative texts, and stories, which were delivered through storytelling, story reading, and movie watching. The narratives used as the media to teach character education were proven to contain character values such as religious value, honesty, tolerance, discipline, hard work, creativity, independence, democracy, intelligence and curiosity, nationalism, patriotism, appreciation, friendliness, love of peace, reading interest, environmental awareness, social awareness, and responsibility. This implies that the use of various forms of narrative from an early age can support the formation of children's character and the importance of utilizing various stories in character education pedagogy and curriculum.